1996
DOI: 10.1038/bjc.1996.590
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of murine mammary carcinoma metastasis with interferon γ and MHC gene-transduced tumour cells

Abstract: Summary Gene-transfected tumour cells were used to cure mice bearing lung metastases by the parental, nontransduced mammary adenocarcinoma (TSA-pc). Repeated subcutaneous (s.c.) administrations of mitomycin C (MitC)-treated interferon y (IFN-y) transfectants induced a 90% inhibition in the number of lung metastases. Therapeutic effect required an intact T-cell response, as shown by the lack of efficacy in nude mice. Autocrine stimulation by IFN-y induces specific modifications in the phenotype of transfectants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…33 We did not test D d expression, as previous reports have shown that H -2D d TS /A expression levels are comparable with K d class I expression levels. 34 The B16.F10 subclone used in this study expresses low levels of H -2K b and H -2D b class I MHC molecules in vitro (Fig 1A ) . On the opposite, the B16K1 cells, which are a clone of B16.F10 cells which was transfected with H -2K b genes 31 express high levels of H -2K b (Fig 2D).…”
Section: Resultsmentioning
confidence: 92%
“…33 We did not test D d expression, as previous reports have shown that H -2D d TS /A expression levels are comparable with K d class I expression levels. 34 The B16.F10 subclone used in this study expresses low levels of H -2K b and H -2D b class I MHC molecules in vitro (Fig 1A ) . On the opposite, the B16K1 cells, which are a clone of B16.F10 cells which was transfected with H -2K b genes 31 express high levels of H -2K b (Fig 2D).…”
Section: Resultsmentioning
confidence: 92%
“…26 B16 is a murine breast cancer cell line and 4T1 is a murine melanoma cancer cell. The cells were cultured in complete medium consisting of Rosewell Park Memorial Institute (RPMI) 1640, 10% heat-inactivated fetal bovine serum, 0.1 mM non-essential amino acids, 1 mM sodium pyruvate, 50 mM 2-Methoxy-1-ethanol (2-ME), 0.3% glutamine, 100 U/ml penicillin G sodium, 100 mg/ml streptomycin sulfate and 0.25 mg/ml amphotericin B (Life Technologies, Rockville, MD).…”
Section: Cell Linementioning
confidence: 99%
“…As adjuvants, IFN-g and GM-CSF have been shown to enhance tumor antigen-specific effects. 26,33 Enhanced production of IFN-g, GM-CSF and TNF-a are involved in tumor antigen-specific immunity. Prolonged and enhanced secretion of IFN-g by CD4 þ T cells may contribute to maintenance of an effective TERT-specific immune response and break immune tolerance.…”
Section: Tert Expression In Tumorsmentioning
confidence: 99%
See 2 more Smart Citations